PENGARUH PENDIDIKAN KESEHATAN TERHADAP UPAYA PENCEGAHAN PENULARAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS MUARA KUMPEH - Ahmad Syaripi; Vevi Suryenti; Giat Wantoro (Jurnal Akademika Baiturrahim Jambi, 2016)
Background: Tuberculosis is an infectious disease caused by rod-shaped bacteria (bacilli), recognized as mycobacterium tuberculosis. The total of TB patients were; in year 2012 as many as 48 people; in 2013 as many as 72 people; while in 2014 as many as 62 peopleAt the public health center MuaraKumpeh.Transmission of this disease through the intercession of saliva or sputum of patients containing pulmonary tuberculosis bacillus. People frequently have lack of attitude and concentration to the habit of covering the mouth when got a cough. The impact of the spread of TB bacteria will more quickly attack healthy people, if they are at moist home, light and dense residential. This research aimed to determine the effect of health education toward prevention of transmission of lung tuberculosis. Method: This research was pre experiment research by using one group pretest design – posttest design. Sample is taken by using total sampling technique, and the number ofsamples was 22 respondents. This research was conducted at the public health center MuaraKumpeh in tuberculosis patients from August 15th – 22nd 2015. Data were analyzed through univariate and bivariate by T-test with significance level 95% and α : 5%. Result: The findings were indicated that there was the effect of health education toward prevention of transmission of lung tuberculosis at the public health center MuaraKumpeh with p-value = 0.000 < α = 0.05.  Conclution: It is concluded that there was the effect of health education toward prevention of transmission of lung tuberculosis. The role of health workers (coordinator of pulmonary TB) are still limited to carry out treatment, counseling, and they do not find new cases out actively yet. It is suggested that the public health center MuaraKumpeh should increase the prevention program through a variety of ways health promotion, and the role of the officer in implementing the strategy DOTS